Agronomic and molecular characterization of Chloris gayana cultivars and salinity response during germination and early vegetative growth - Ribotta, Andrea Noemi; Lopez Colomba, Eliana; Bollati, Graciela P.; Striker, Gustavo Gabriel; Carloni, Edgardo José; Griffa, Sabrina Mariana; Quiroga, Mariana Paola; Tommasino, Exequiel Arturo; Grunberg, Karina (CIAT, 2020)
Chloris gayana is a warm-season grass, often cultivated in areas where soil salinity is a major constraint for forage production. Five cultivars (2 unselected populations and 3 synthetic varieties) were evaluated through agronomic traits as well as Inter Simple Sequence Repeats (ISSRs) and Sequence-related Amplified Polymorphism (SRAP) molecular markers. The consensus between both agronomic and molecular data sets was high (>99%) suggesting that both systems provided similar estimates of genetic relationships. The analysis revealed that synthetic varieties, Finecut, Topcut and Santana, were the most genetically different cultivars, whereas the unselected populations, Pioneer and Katambora, were closely related. Responses to salinity stress during germination and early vegetative growth stages were evaluated in only the synthetic varieties. The results showed that Finecut and Santana were able to germinate in the same proportion as controls even at concentrations of 200 mM NaCl. Under hydroponic conditions, Santana attained approximately 20% higher total dry weight than the other 2 varieties and the longest roots. Finecut presented the highest root dry weight. These results suggested that Santana and Finecut showed high salinity tolerance at germination and early vegetative growth stages, both crucial phases when seeking a successful pasture establishment, particularly in saline environments. Further studies in the field are needed to determine if these hydroponic results are reproduced under field conditions.